The treatment of gender in feminist Utopias. - Ng, Timothy Yi Peng. (2012)
Utopia, a genre whose name was first coined by Thomas More in a similarly titled book, carries with it two meanings in its name. It can be used to describe a “good place” or “no place”, depending on how one reads the Greek pun that is intrinsic in reading the book and the genre. With these paradoxes of “good place” and “no place” as well as the complexities of gender in mind, feminist utopian writers add a further dimension of involution to their writing, one that blends in or highlights the themes of gender in these “good place[s]” that they create, simultaneously knowing that such utopias are doubly hard to create in their respective patriarchal societies, and ever so easy to be dismissed as a place that will never exist within the oppressive male-centric constructs the writers were writing in. Thus, within this maelstrom of a genre that is feminist utopian writing, this essay seeks to focus specifically on the treatment of gender and how they differ within the three works of feminist utopias that will be covered: The first being Herland by Charlotte Perkins Gilman, the second a piece of science-fiction writing by Ursula Le Guin, namely The Left Hand of Darkness. The last text of this essay will be The Female Man by Joanna Russ.